Linguistic Genocide or Superdiversity? New and Old Language Diversities - Saarikivi, Janne; Toivanen, Reetta (Linguistic Diversity and Language Rights, 2016)
Are we facing an immense wave of language death or a period of remarkable new linguistic variation? Or both? This book answers this question by analysing studies of language endangerment and loss along with those of language change, revitalization and diversity. Using case studies from Russia and the EU, the authors compare historical language variation to that of the present day, arguing that accelerated language extinction can be considered a result of colonization, modernization and globalization, but so too can many new creoles, intertwined and mixed languages, new ethnic identities, new groups of urban dwellers or migrant groups, all with their own distinct cultural traits. The book therefore surmises that the linguistic heritage of today is simultaneously more endangered and more diverse than ever before